Profesionalisme Jurnalis TV di Era Disruptif Media (Studi Kasus Jurnalis Celebes TV Kota Makassar) - Alem Febri Soni; Muannas Muannas; Teti Novianti (Universitas Negeri Makassar, 2021)
This study aims to determine the level of professionalism among television celebrity journalists in the age of media disruption. The research method used is qualitatively descriptive. with a case study approach, namely the research carried out that is focused on a particular case and needs to be carefully observed and analyzed to completion. The results of this study show that Celebes television journalists, in performing their duties and jobs as press representatives, understand methods of reporting and presenting news based on the objectivity of data and in accordance with the facts in the field. The professionalism of journalistic work is highly valued in the current era of disruption, always referring to the press law and adhering to the journalistic code of ethics. Celebes television journalists are able to provide accurate, balanced information to sources by reviewing data and reflecting on different perspectives or news angles in an event.Keywords: Journalist, Professionalism, Disruption, Celebes Tv, Journalistic Code of Ethics